Integrasi Musik digital dan Artificial Intelligence: Analisis Interaksi Simbolik Pada Proyek Musik AIAIQ - Fajriansyah, Muhammad Nur; Ardiyanti, Handrini (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2024)
This research explores the application of symbolic interaction theory in collaboration between producers and musicians in the digital music production process, with a focus on the AIAIQ project, which integrates artificial intelligence (AI). This research examines how AI influences symbolic interactions in the music production process, especially in interpreting musical emotions and communication dynamics. This research resulted from an empirical study using a qualitative approach; this approach was used to gain an in-depth understanding of symbolic interactionism. Data sources were obtained from observations and interviews. The results of this research show that although artificial intelligence (AI) can improve technical efficiency, it can also change the dynamics of traditional social and non-verbal communication that are important for creative collaboration. By analyzing the role of human experience in interpreting AI-generated music and changes in interaction patterns, this research highlights the limitations and challenges faced by AI in maintaining the depth of human interaction in the creative process.